Diversi dalam Proses Hukum Tindak Pidana Anak: Studi Kasus Putusan Nomor 10/PID.SUS-ANAK/2024/PN UNR - Aliffia Intan Maharani; Diandra Preludio Ramada (Jurnal Hukum Lex Generalis, 2025)
Diversion is an alternative to formal criminal proceedings for juvenile offenders that focuses on restorative justice. In decision No. 10/Pid.Sus Anak/2024/PN Unr, a procedural settlement was attempted, but it failed due to the economic disparity between the perpetrator and the victim. Despite the fact that the peace process had not proceeded smoothly, the judge still imposed a non-criminal sentence to safeguard the child's future. This study indicates that the success of diversion does not solely depend on legal procedures but also on the social readiness and fairness of the parties involved in resolving the conflict equitably. A deep understanding of the importance of restorative efforts is crucial for the effective implementation of diversion.